Self-reported Occupational-related Contact Dermatitis: Prevalence and Risk Factors among Health-care Workers in Saudi Arabia: A Cross-sectional Study - Rahaf I. Alshareef; Abeer R. Alkahtani; Areej R. Alkahtani; Norah A. Albdaya; Mohammed S Aldossary (Journal of Dermatology and Dermatologic Surgery)
Background: Occupational skin disease is the second-most common occupational disease according to the Centers for Disease Control and Prevention, accounting for 30%–45% of all occupational diseases worldwide, and out of which 95% is contact dermatitis. Health-care workers are at high risk of developing occupational contact dermatitis (OCD). Purpose: The purpose of the study was to investigate the prevalence of and risk factors for OCD among health-care workers in Saudi Arabia. Methods: This cross-sectional study was conducted from July to August 2023 after obtaining ethical approval from the institutional review board of the Ministry of Health. We used a newly generated English questionnaire based on the Nordic Occupational Skin Questionnaire (2002). Results: Overall, 592 health-care professionals were included; 141 had OCD on hands, wrists, or forearms. Most respondents with OCD (66.0%, n = 93) were women, whereas 48% (34.0) were men. Among health-care professionals, OCD was common in doctors; 81 out of 321 reported having the condition. The crude odds ratio for personal and family history of allergy were 3.88 (95% confidence interval (CI): 2.62–5.82), and 2.63 (95% CI: 1.75–4.00), respectively, suggesting that participants with these comorbidities had a higher chance of developing OCD than patients without them did. Conclusion: OCD is common among health-care professionals in Saudi Arabia. Awareness of disease preventive measures may help improve outcomes.